2020
DOI: 10.5852/ejt.2020.720.1113
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the lanternfly genus Limois Stål, 1863 (Hemiptera: Fulgoromorpha: Fulgoridae) with description of a new species from China

Abstract: All extant species of the planthopper genus Limois Stål (Hemiptera: Fulgoromorpha: Fulgoridae) were studied. One new species, Limois sordida sp. nov., is described and illustrated from China. Six known species are re-described and photos and illustrations of male genitalia are provided. A key to all extant species of this genus is also given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 777 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…After morphological identification, the thoracic muscle tissue was used to extract total genomic DNA using the DNeasy DNA Extraction kit (Qiagen). Species identifications were based on Melichar (1912) [15] for the genus Dichoptera, Wang et al (2020) [16] for the genus Limois, Constant and Pham (2018) [17] for the genus Neoalcathous, Constant (2010) [18] for the genus Penthicodes and Nagai and Porion (1996) [19] for the genus Pyrops.…”
Section: Sample Collection and Dna Extractionmentioning
confidence: 99%
“…After morphological identification, the thoracic muscle tissue was used to extract total genomic DNA using the DNeasy DNA Extraction kit (Qiagen). Species identifications were based on Melichar (1912) [15] for the genus Dichoptera, Wang et al (2020) [16] for the genus Limois, Constant and Pham (2018) [17] for the genus Neoalcathous, Constant (2010) [18] for the genus Penthicodes and Nagai and Porion (1996) [19] for the genus Pyrops.…”
Section: Sample Collection and Dna Extractionmentioning
confidence: 99%
“…As a result, Kinmen Islands are a possible origin of invasion. Previous studies have reported the longan lanternfly as an agricultural pest [15,19,20], but no significant impact has been observed since its invasion. Nevertheless, the ecological effects of invasive species are unpredictable.…”
Section: Introductionmentioning
confidence: 99%
“…The adult longan lanternfly, Pyrops candelaria (L.), has long been known for its colorful, spectacular appearance and typical cephalic process. It causes economic losses by sucking the juice from the trunk of fruit trees [1][2][3]. According to Lin et al [4], the longan lanternfly invaded Taiwan probably from the Kinmen Islands or Hong Kong.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of the specific host plants for immature stages of the insect may also be important for the establishment of a population in a possible new habitat. Before invading Taiwan, the distribution of the longan lanternfly includes China (Guangxi, Hainan, Guangdong, Fujian, Hong Kong), India, Malaysia, Thailand, Vietnam, Cambodia, Indonesia, and Sikkim [1,5]. Several fruit trees including longan, litchi, olive, orange, and mulberry suffered from its feeding on the trunk and cortex of the trees [1,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation